The New England mind, from colony to province - Miller, Perry, 1905-1963 (Belknap Press of Harvard University Press, 1983)
The New England Mind: From Colony to Province is one of Perry Miller's masterworks, exploring the intellectual history of the Puritans through a deep investigation of the thought of the Puritan divines. In this book, as well as its predecessor The New England Mind: The Seventeenth Century, Miller asserts a single intellectual history for America that could be traced to the Puritan belief system.